2021
DOI: 10.3390/polym13162691
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Thermo-Mechanical Properties of Epoxy Composites Using Fumed Silica with Different Surface Treatment

Abstract: The objectives of this study are to improve the thermal and mechanical properties of epoxy/fumed silica composite with different surface treatments of fumed silica. The addition of silica nanoparticles improved the thermal stability of the composite and slowed down the pyrolysis process. The crosslinking density and Tg of the epoxy/fumed silica composites increased because of the interfacial interaction between the PDMS-treated fumed silica particles and the epoxy matrix. The flexural strength of the epoxy nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The observation is in line with previous studies, which suggest that merely a few percent volume fraction of fumed silica is able to form a three-dimensional network within the polymer composite 32 . Fumed silica, which has been reported as an inorganic filler to mechanically reinforce polymer matrixes 33 , 34 , may result in better structural stability of the structural scaffold against gravitational and capillary forces with less structural deformation during the drying process. To verify the mechanical reinforcement of the polymer matrix by adding fumed silica, we conducted a compressive test on non-porous films with different fumed silica content (PC and FSPC) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observation is in line with previous studies, which suggest that merely a few percent volume fraction of fumed silica is able to form a three-dimensional network within the polymer composite 32 . Fumed silica, which has been reported as an inorganic filler to mechanically reinforce polymer matrixes 33 , 34 , may result in better structural stability of the structural scaffold against gravitational and capillary forces with less structural deformation during the drying process. To verify the mechanical reinforcement of the polymer matrix by adding fumed silica, we conducted a compressive test on non-porous films with different fumed silica content (PC and FSPC) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The larger particle size of FSNs reduces their production cost to 10 % of that of NS particles, facilitating their wide applications in anti-aging rubber applications 53 . Due to the use of nanoparticle chain aggregates as a basic unit 54,55 , fumed silica can be employed as fillers to improve the rheological properties of resins and coatings. To recapitulate, previous studies have demonstrated that NS plays a crucial role in increasing the bitumen's resistance to aging.…”
Section: Inhibitors Of Bitumen Agingmentioning
confidence: 99%
“…In recent years, much research has been reported on the improvement of the tensile strength, thermal stability and storage modulus of epoxy composites with the incorporation of fillers into the epoxy matrix. [17][18][19][20] When choosing fillers, various characteristics of filler particles need to be considered, such as their size, shape and aspect ratio, specific surface area (SSA), distribution and dispersion, as well as loading. 21 Today, most SMs are mainly composed of barium sulfate (BaSO 4 ) as the filler.…”
Section: Introductionmentioning
confidence: 99%